2020
DOI: 10.1002/ejoc.201901906
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed One‐Pot A3‐Coupling/1,5‐Hydride Shift/Schmittel‐Type Cyclization: From Aldehydes, Amines and Alkynes to the Synthesis of Benzo[b]fluorenes

Abstract: A step‐economic gold‐catalyzed one‐pot synthesis of benzo[b]fluorenes, from aldehydes, alkynes and amines, proceeding via an A3‐coupling/1,5‐hydride shift/Schmittel‐type cyclization is described. The formation of the allene intermediate is not dependent on a previous installation of reaction triggers, and upon cyclization delivered benzo[b]fluorenes. With this method, just by an easy modification of the starting materials in a modular way, nineteen benzo[b]fluorenes, bearing different substituents Ar1, Ar2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 54 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…It is important to highlight that for an unbiased determination of the structures of benzo[b]fluorene 6a, X-ray crystallography analysis was performed (Figure 1). [10] Figure 1. Solid state molecular structure of 6a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to highlight that for an unbiased determination of the structures of benzo[b]fluorene 6a, X-ray crystallography analysis was performed (Figure 1). [10] Figure 1. Solid state molecular structure of 6a.…”
Section: Resultsmentioning
confidence: 99%
“…Solid state molecular structure of 6a. [10] Under these optimized conditions ( Table 2, entry 2) the scope of the reaction was explored. We started to explore the scope of this reaction by modifying the electronics of the aldehyde in both Ar 1 and Ar 2 .…”
Section: Resultsmentioning
confidence: 99%
“…An overwhelming reaction that is recognized to present a onestep or stepwise mechanism, depending on the electronic nature of reactants, is the C 2 -C 6 enyne-allene cyclization, also called Schmittel cyclization, [1][2][3][4][5][6] which has received interest due to its capability to abstract hydrogen and DNA strand cleavage. Schmittel et al reported for the first time this cyclization reaction, 1,2 which corresponded to intramolecular C 2 -C 6 cyclization of hepta-1,2,4-triene-6-yne to produce a five-membered cyclic structure (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Schmittel and co-workers reported a regioselective thermal C 2 –C 6 cyclization of benzoenyne–allene bearing aryl groups in 1996 to construct the benzo­[ b ]­fluorene ring (Scheme , a) . Since then, this intramolecular cyclization has been developed and applied in the synthesis of benzo­[ b ]­fluorene derivatives via the formation of benzoenyne–allene intermediates in situ under different conditions . On the other hand, in 2011, Wang and co-workers reported a convenient formation of allenes by a copper­(I)-catalyzed coupling reaction of N -tosylhydrazones and terminal alkynes via a metal carbene migratory insertion process in the presence of base, and then this allene formation step was well-applied in the construction of aromatic compounds via the cascade cyclization .…”
Section: Introductionmentioning
confidence: 99%